Black American Communities: From Pathology to Intersectionality (British Journal of Multidisciplinary and Advanced Studies, 2024)
This article, using Mocombeian phenomenological structural theory, phenomenological structuralism, highlights black American community transition from a pathological-pathogenic community to an intersectional one, which dominates the contemporary global order.  The work posits that the constitution of black American communities and their identities have been the product of their relations to the means and mode of production within the Protestant Ethic and the spirit of capitalism.  As such, black Americans have never been agents in the constitution of their own identities.  They have always been and remain (reactionary) pawns of capital seeking, dialectically or negative dialectically, to integrate the American social structure.  Contemporarily, their integration in post-industrial America is marked by their transition from a pathological-pathogenic community to a neoliberal intersectional one dominated by their youth, women, and queers.